Penerapan Metode Cerita Untuk Meningkatkan Kemampuan Berbahasa dalam Mata Pelajaran Bahasa Indonesian di Kelas III Sekolah Dasar - Niken Ayu Murti; Armiya Nur Lailatul Izzah; Moh Imam Al Ghofiqi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to describe the effectiveness of the storytelling method in improving the language skills of elementary school students. The subjects of this research were the third-grade students of SDN 2 Doplang. The findings indicate that the implementation of the storytelling method significantly enhances students’ listening, speaking, and writing abilities. The learning process, which was initially conventional, became more interactive, enjoyable, and meaningful. Teachers play a crucial role as communication role models and as creators of a safe and positive learning environment, enabling students to express their ideas with greater confidence. In addition, parental involvement through parenting forums further strengthened students’ learning outcomes at school. The use of audiovisual media in storytelling activities also proved effective in increasing students’ engagement and comprehension of the material. These findings demonstrate that the storytelling method not only develops language proficiency but also fosters character values such as honesty, courage, empathy, and responsibility. Therefore, the storytelling method serves as an innovative, integrative, and humanistic strategy for enhancing Indonesian language learning in elementary schools.